An exploratory study on UNAM's opportunities of being an entrepreneurial university - Shiimi, Victoria (Rhodes University, Faculty of Commerce, Rhodes Business School, 2020)
Universities, especially those publicly funded by the government are at the edge of the economic woes when budget allocation is cut to support their operations. University should not only focus on research and the traditional role of teaching but, to become innovative by creating third stream income generation projects and activities. This would enable them to bridge the gap in financing from the state. The main goal of the study is to explore whether the university has opportunities to become entrepreneurial. The researcher analyzed the study from the perspective of internal capabilities the institution owns and how these capabilities can be applied to create a competitive advantage and external opportunities for the institution. To achieve the objectives of this study, the researcher employed a case study research design approach. The study was embedded in the interprevists paradigm and, following an inductive approach. The study had a population of 14 Centres at UNAM where a sample of 4 Centres was purposively selected to represent the population because they were responsible for research and entrepreneurship activities. Documents review and semi-structured interviews were used to collect secondary and primary data respectively, which helped in the triangulation to avoid data error. These methods also allowed the researcher to ensure credibility, transferability, trustworthiness and external validity. To adhere to all ethical regulations and procedures, the researcher obtained the ethics approval from the Rhodes Ethics Committee, which, was then used to obtain Gatekeeper permission from UNAM. The study found that UNAM has the internal capabilities required that provides them an opportunity to become entrepreneurial. Through its Innovation and Development Department in collaboration with Inceptus, a UNAM commercial owned holding company. The study recommended that UNAM put structures in place, to begin with, all entrepreneurial projects towards securing third stream income as well as expanding research that focuses on leadership and governance.
Keywords: Entrepreneurship -- Namibia; Academic-industrial collaboration -- Namibia; Education, Higher -- Aims and objectives -- Namibia; University of-- Namibia. Innoviation and Development Department; University of-- Namibia -- Finance; Education, Higher -- Economic aspects -- Namibia; Education, Higher -- Namibia -- Finance